Persepsi Siswa Tentang Pembelajaran Berbasis Produksi Dalam Kelompok Pelajaran Produktif - Fitra Prima Wulansari; Amos Neolaka; Rosmawita Saleh (Jurnal Pensil : Pendidikan Teknik Sipil, 2013)
The objective of this study for knowing student perception about based production learning of lesson productive group. Research location in SMK N 4 Jakarta, SMK N 52 Jakarta and SMK N 58 Jakarta, This research used survey method with scale likert 4-1. Research population in this case is grade X students Furniture Engineering and Wood Construction Engineering competence qualification 2011/2012 as much as 117 students. Total samples is 45 students and sampling quota to take it. Used a questionary to get data student perception about based production learning of lesson productive group. Research result about based production learning of lesson productive group in perception totality indicator have 97,5 an average point, Integrity aspect indicator have 99,75 an average point, Oncoming lesson indicator and technology have 107,17 an average point, Design lesson indicator have 95,38 an average point, Development system lesson indicator have 101,3 an average point, Media for lesson indicator have 99 an average point, Processing lesson student have 107,83 an average point, Rating of lesson indicator have 95,38 an average point.The result that based production learning have been good to be implemented, with the existence of subjects productive and unit of production at school could increased the motivation students at the time of the learning process. However more keep increased because school is the comfortable place for learning centre to students and enhancement teach skill for teacher with following the technology and information about education world